Penggunaan Media Puzzle untuk Meningkatkan Pemahaman Konsep Luas Gabungan Bangun Datar pada Peserta Didik Kelas V - Sari, Devina Mukti; Mukmin, Bagus Amirul; Putra, Aji Setya Gaya (PTK: Jurnal Tindakan Kelas, 2025)
The low level of students' understanding of the concept of combined area of ​​flat shapes indicates the need for more interactive and concrete learning strategies. The purpose of this study was to improve the understanding of the concept of combined area of ​​flat shapes in grade V students of SDN Burengan 2 Kediri through the use of puzzle media. This study used the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which was carried out in two cycles, with 28 students as subjects. The results showed an increase in learning completeness from 25% in the pre-cycle (average value of 71.1), to 53.6% in cycle I (average 74.2), and increased significantly to 89.3% in cycle II (average 80). The use of puzzle media has proven effective in improving students' understanding in a concrete, fun, and collaborative manner.